WORKSHOP PENGUATAN KOMPETENSI SISWA SMA DI KOTA PADANG MENUJU OLIMPIADE SAINS NASIONAL (OSN) IPA DAN MATEMATIKA TINGKAT NASIONAL - Mildawati Mildawati; Solfiyeni Solfiyeni; Mairawita Mairawita; Fuji Astuti Febria; Muhammad Samudra Ilham; Zulfi Zulfi; Yefrida Yefrida; Imelda Imelda; Afdhal Muttaqin; Narwen Narwen; Efendi Efendi; Mahdivan Syafwan (Universitas Nusa Bangsa, 2024)
The National Science Olympiad (OSN) is a prestigious event that involves the best students from various levels of education who have passed a rigorous selection at the district and provincial levels. One way to improve the quality of students in facing the OSN in Science and Mathematics is through structured coaching. The OSN Science and Mathematics Workshop held around the UNAND campus in Padang City is one such effort that has proven successful. The objectives of this workshop include three main aspects, namely improving the competence of high school students in basic science and mathematics, improving students' skills in solving OSN questions and improving the quality of high school education in Padang City. The workshop consisted of three main stages: planning, implementation, and evaluation. In the planning stage, OSN questions from the previous year were collected to be used as learning materials. The implementation stage involved a series of activities, including a pre-test, structured learning through lectures, question simulations, and discussions using audiovisual aids. The evaluation was conducted through a post-test to measure the improvement of students' understanding after attending the workshop. The results of this workshop showed a significant increase in the understanding of students who had participated from 30% to 60%. This illustrates the effectiveness of a sustainable and structured approach in improving student competencies to face OSN competitions in Science and Mathematics. This workshop could become a model for efforts to improve the quality of education in schools around the campus. It can be an inspiration for other educational institutions. Keywords: National Science Olympiad (OSN), Senior High School, workshop Abstrak Olimpiade Sains Nasional (OSN) adalah ajang prestisius yang melibatkan siswa-siswa terbaik dari berbagai tingkatan pendidikan yang telah melewati seleksi ketat di tingkat kabupaten dan provinsi. Salah satu cara meningkatkan kualitas siswa menghadapi OSN bidang IPA dan Matematika adalah melalui pembinaan terstruktur. Workshop OSN IPA dan Matematika yang diselenggarakan di sekitar kampus Universitas Andalas (UNAND) di Kota Padang adalah salah satu upaya yang telah terbukti berhasil. Tujuan dari workshop ini mencakup tiga aspek utama, yaitu meningkatkan kompetensi, keterampilan, dan mutu pendidikan siswa SMA dalam ilmu dasar IPA dan Matematika di Kota Padang. Workshop ini terdiri dari perencanaan, pelaksanaan, dan evaluasi. Pada tahap perencanaan, soal-soal OSN dari tahun sebelumnya dikumpulkan sebagai bahan pembelajaran. Tahap pelaksanaan, dilakukan pre-test, ceramah, simulasi soal, dan diskusi dengan peralatan audiovisual. Evaluasi dilakukan post-test untuk mengukur tingkat pemahaman siswa setelah workshop. Hasilnya, terjadi peningkatan signifikan dalam pemahaman soal OSN, yaitu dari 30% menjadi 60%. Hal ini menggambarkan efektivitas pendekatan berkelanjutan dan terstruktur dalam meningkatkan kompetensi siswa untuk menghadapi kompetisi OSN bidang IPA dan Matematika. Workshop semacam ini berpotensi menjadi model upaya peningkatan kualitas pendidikan di sekolah sekitar kampus dan dapat menjadi inspirasi bagi lembaga pendidikan lain. Kata Kunci: Olimpiade Sains Nasional (OSN), SMA, workshop